Vocational High School Management Model-Center of Excellence in North Sulawesi Province - Sumual, Herry; Sompotan, Grace J.; Sumual, Hendro (International Journal of Information Technology and Education, 2024)
Vocational education and training will be further strengthened as the development strategy shifts from physical infrastructure to human development. This study aims to determine the implementation of human resource development carried out by schools and to produce a draft of a human resource development model based on the Knowledge View. The method used in this study is a qualitative approach with a case study method. This method is used to obtain needs analysis data in designing a human resource development model in vocational education. The results of this study indicate that the human resource development model is carried out in schools. Vocational schools are expected to have the ability Vocational schools are expected to have the ability and capability to respond to external demands such as the business world and the industrial world. This study concludes that Human resource development in State Vocational High Schools in Manado City has been implemented from planning to implementation.